Tissue mRNA for S100A4, S100A6, S100A8, S100A9, S100A11 and S100P Proteins in Colorectal Neoplasia: A Pilot Study - Peterova, Eva; Bures, Jan; Moravkova, Paula; Kohoutova, Darina (Molecules (Basel, Switzerland), 2021)
S100 proteins are involved in the pathogenesis of sporadic colorectal carcinoma through different mechanisms. The aim of our study was to assess tissue mRNA encoding S100 proteins in patients with non-advanced and advanced colorectal adenoma. Mucosal biopsies were taken from the caecum, transverse colon and rectum during diagnostic and/or therapeutic colonoscopy. Another biopsy was obtained from adenomatous tissue in the advanced adenoma group. The tissue mRNA for each S100 protein (S100A4, S100A6, S100A8, S100A9, S100A11 and S100P) was investigated. Eighteen biopsies were obtained from the healthy mucosa in controls and the non-advanced adenoma group (six individuals in each group) and thirty biopsies in the advanced adenoma group (ten patients). Nine biopsies were obtained from advanced adenoma tissue (9/10 patients). Significant differences in mRNA investigated in the healthy mucosa were identified between (1) controls and the advanced adenoma group for S100A6 (p = 0.012), (2) controls and the non-advanced adenoma group for S100A8 (p = 0.033) and (3) controls and the advanced adenoma group for S100A11 (p = 0.005). In the advanced adenoma group, differences between the healthy mucosa and adenomatous tissue were found in S100A6 (p = 0.002), S100A8 (p = 0.002), S100A9 (p = 0.021) and S100A11 (p = 0.029). Abnormal mRNA expression for different S100 proteins was identified in the pathological adenomatous tissue as well as in the morphologically normal large intestinal mucosa.
Keywords: Colorectal Neoplasms; kalgranulin B; nádorové proteiny; Humans; Case-Control Studies; protein S100A6; messenger RNA; Calgranulin B; lidé středního věku; studie případů a kontrol; Biomarkers, Tumor; colorectal neoplasia; Calcium-Binding Proteins; Female; Aged; S100 proteins; S100 Calcium Binding Protein A6; senioři; lidé; Calgranulin A; Cell Cycle Proteins; pilotní projekty; Pilot Projects; S100 Calcium-Binding Protein A4; nádorové biomarkery; RNA, Messenger; S100 kalcium vázající protein A4; ženské pohlaví; Follow-Up Studies; kolorektální nádory; Male; S100 Proteins; Middle Aged; mRNA; prognóza; proteiny vázající vápník; proteiny buněčného cyklu; adenom; Adenoma; kalgranulin A; Neoplasm Proteins; mužské pohlaví; large intestine; Prognosis; následné studie; proteiny S100